Photodriven Active Ion Transport Through a Janus Microporous Membrane. (24th February 2020) - Yang, Jinlei; Liu, Pengchao; He, Xiao; Hou, Junjun; Feng, Yaping; Huang, Zhiwei; Yu, Lian; Li, Lianshan; Tang, Zhiyong
Abstract: Precise control of ion transport is a fundamental characteristic for the sustainability of life. It remains a great challenge to develop practical and high‐performance artificial ion‐transport system that can allow active transport of ions (protons) in an all solid‐state nanoporous material. Herein, we develop a Janus microporous membrane by combining reduced graphene oxide (rGO) and conjugated microporous polymer (CMP) for controllable photodriven ion transport. Upon light illumination, a net ionic current is generated from the CMP to the rGO side of the membrane, indicating that the rGO/CMP Janus membrane can realize photodriven directional and anti‐gradient ion transport. Analogously to the p‐n junction in photovoltaic devices, light is firstly converted into separated charges to trigger a transmembrane potential, which subsequently drives directional ion movement. For the first time, this method enables integration of a photovoltaic effect with an ionic field to drive active ion transport. With the advantages of scaled up production and easy fabrication, the concept of photovoltaic ion transport based on Janus microporous membrane may find wide application in energy storage and conversion, photodriven ion‐sieving, and water treatment. Abstract : Eine mikroporöse Janus‐Membran aus reduziertem Graphenoxid/konjugiertem mikroporösem Polymer (rGO/CMP) wurde hergestellt, die sich die hohe Massentransporteffizienz einer mikroporösen Membran und die effiziente Elektronen‐Loch‐Trennung einer Janus‐Architektur zunutze macht. Die photoinduzierte Elektronen‐Loch‐Trennung erzeugt ein Transmembran‐Potential, das den aktiven und gerichteten Ionentransport antreibt.